The C-mannosylome of human induced pluripotent stem cells implies a role for ADAMTS16 C-pannosylation in eye development - Cirksena, Karsten; Hutte, Hermann J.; Shcherbakova, Aleksandra; Thumberger, Thomas; Sakson, Roman; Weiss, Stefan; Jensen, Lars Riff; Friedrich, Alina; Todt, Daniel; Kuss, Andreas W.; Ruppert, Thomas; Wittbrodt, Joachim; et al. (Molecular & cellular proteomics, 2021)
C-mannosylation is a modification of tryptophan residues with a single mannose and can affect protein folding, secretion, and/or function. To date, only a few proteins have been demonstrated to be C-mannosylated, and studies that globally assess protein C-mannosylation are scarce. To interrogate the C-mannosylome of human induced pluripotent stem cells, we compared the secretomes of CRISPR-Cas9 mutants lacking either the C-mannosyltransferase DPY19L1 or DPY19L3 to WT human induced pluripotent stem cells using MS-based quantitative proteomics. The secretion of numerous proteins was reduced in these mutants, including that of A Disintegrin And Metalloproteinase with ThromboSpondin Motifs 16 (ADAMTS16), an extracellular protease that was previously reported to be essential for optic fissure fusion in zebrafish eye development. To test the functional relevance of this observation, we targeted dpy1911 or dpy1913 in embryos of the Japanese rice fish medaka (Oryzias latipes) by CRISPR-Cas9. We observed that targeting of dpy1913 partially caused defects in optic fissure fusion, called coloboma. We further showed in a cellular model that DPY19L1 and DPY19L3 mediate C-mannosylation of a recombinantly expressed thrombospondin type 1 repeat of ADAMTS16 and thereby support its secretion. Taken together, our findings imply that DPY19L3-mediated C-mannosylation is involved in eye development by assisting secretion of the extracellular protease ADAMTS16.